"What's wrong with mak?": understanding menopause among young Malay adults - Mohamad Diah, Nurazzura (2009)
Menopause is a time of life where women make the transition from a reproductive stage to a non-reproductive stage. This transition (and all that it entails in terms of symptoms and discomfort) is kept secret and women do not tell family members about their experiences. In most instances, information about menopause and issues related to it is passed on by friends who are older or the nearest kin, other than the parents. Objective: The aim of this study is to explore how young Malay adults actually come to understand what menopause is as well as its related symptoms. Methods: This study employs ethnographic methods (participation observation and in-depth interviews) with a sample of fourteen young Malay adults aged 24-38. All of them have mothers who are experiencing menopause. Qualitative approach was used to analyze data. Results: Knowledge about menopause in urban Malay society is transmitted by their mothers’ capacity to engage in prayer, fasting and the teaching of religion. On the other hand, stories about menopause were told ‘around’ rather than ‘about’ menopause. With regard to mood swings and sensitiveness, these symptoms have to some degree altered their communication with their mothers. These children expressed concern for their mothers acting out of character outside the house and would do their best to please them in words and behaviour. Conclusion: Family members remain confused or unsure of what is happening and how best to respond to their mothers’ behaviour due to menopause. They only learn about menopause through informal ways, particularly through observation.